Vibrating Makes for Better Seeing: From the Fly’s Micro-Eye Movements to Hyperacute Visual Sensors - Viollet, Stéphane (Frontiers in Bioengineering and Biotechnology, 2014)
Active vision means that visual perception not only depends closely on the subject's own movements, but that these movements actually contribute to the visual perceptual processes. Vertebrates' and invertebrates' eye movements are probably part of an active visual process, but their exact role still remains to be determined. In this paper, studies on the retinal micro-movements occurring in the compound eye of the fly are reviewed. Several authors have located and identified the muscles involved in these small retinal movements. Others have established that these retinal micro-movements occur in walking and flying flies, but their exact functional role still remains to be determined. Many robotic studies have been performed in which animals' (flies' and spiders') miniature eye movements have been modelled, simulated and even implemented mechanically. Several robotic platforms have been endowed with artificial visual sensors performing periodic micro-scanning movements. Artificial eyes performing these active retinal micro-movements have some extremely interesting properties, such as hyperacuity and the ability to detect very slow movements (motion hyperacuity). The fundamental role of miniature eye movements still remains to be described in detail, but several studies on natural and artificial eyes have advanced considerably toward this goal.